EXTRACTION, PHYSICOCHEMICAL PROPERTIES AND ANTI-MICROBIAL ACTIVITIES OF OIL FROM CITRUS SINENSIS (ORANGE) AND MAESOBOTRYA BARTERI (BUSH CHERRY) SEEDS - Babatolu, Ayotunde Oluwaseun; Akinsuli, V. Olawale; Adekunbi, E. Adedayo; Okoro, O. Sam; Dada, S. Fatima; Babatolu, O. Ibironke (FUDMA JOURNAL OF SCIENCES, 2025)
Oil from seeds of Citrus sinensis and M. barteri were extracted by solvent extraction using n-hexane. The percentage yield of the oil from seeds of Citrus sinensis and M. barteri was ascertained as 36.21 % and 12.56 % respectively. Physicochemical properties of the seed oils of Citrus sinensis and M. barteri were determined using standard methods. The extracted oils were further examined for antimicrobial studies. Nonetheless, oil extracted from Citrus sinensis and M. barteri seeds exhibits notable antimicrobial activity against every tested organism, including fungi and bacteria. However, at a concentration of 200 mg/ml, the oil from Citrus sinensis seeds showed more remarkable and excellent antimicrobial activity against E. coli, S. typhi, and C. albicans than the oil from M. barteri seeds. Therefore, Utilization of these seeds for residential and industrial usage in cosmetics and pharmaceutical will reduce environmental wastes and enrich their commercial value. Additionally, they offer legitimate channels for the pharmaceutical and cosmetic industries to channel these underutilized bio-resources (seeds) into medicines, soaps, and creams.